2014
DOI: 10.4236/abb.2014.512110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Feeding and Process Parameters on Production of Coenzyme Q<sub>10</sub> Using <i>Paracoccus denitrificans</i> ATCC 19367 Mutant Strain P-87

Abstract: Coenzyme Q 10 (CoQ 10 ), an important antioxidant molecule playing a major role in electron transport chain, has been commercially produced by fermentation process for the use in oral nutraceutical formulations. Constructing the high-yielding CoQ 10 producing strains is a pre-requisite for cost-effective production. A superior mutant strain P-87 generated from Paracoccus denitrificans ATCC 19367, which showed 1.25-fold improvement in specific CoQ 10 content higher than the wild type strain at shake flask level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…CoQ10, can be produced by chemical synthesis, extraction from biological tissues (plants and animal) and microbial fermentation (Laplante et al, 2009). In the wake of environmental awareness, the chemical options became least desirable due to inherent uses of solvents and chemicals in the process (Tokdar et al, 2014).…”
Section: Coq10 Effective Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…CoQ10, can be produced by chemical synthesis, extraction from biological tissues (plants and animal) and microbial fermentation (Laplante et al, 2009). In the wake of environmental awareness, the chemical options became least desirable due to inherent uses of solvents and chemicals in the process (Tokdar et al, 2014).…”
Section: Coq10 Effective Sourcesmentioning
confidence: 99%
“…Microbial production offers an environmentally benign option based on the enzymatic catalysis at the cellular level for CoQ10 assembly. Moreover, this approach is attractive to the industry because the process is easy to control at a relatively low production cost (Tokdar et al, 2014). However, due to the limits of CoQ10 accumulation in cells, strain improvements have been made using genetic engineering (using recombinant nucleic acid technology), chemical mutagenesis and high hydrostatic pressure treatment (Kim et al, 2015).…”
Section: Microbial Sources Of Coq10mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, a study assessing the effect of O 2 levels on the production of CoQ 10 in P. denitrificans CCM 982 showed that the highest yield (1.2 mg g −1 ) was obtained at an oxygen concentration of 2.5%, with a decrease in the coenzyme content to 0.43 mg g −1 when the O 2 levels increased to 21% (Kaplan et al, 1993). Recently, the CoQ 10 biosynthesis capacity of a mutant strain of P. denitrificans (P-87) has been evaluated using the precursor parahydroxy benzoic acid (Tokdar et al, 2014). This study revealed a maximum specific cell content of 1.63 mg g −1 , which was only 1.8-fold higher than that obtained in our study with no particular optimization strategy.…”
Section: Process Performance With Methanolmentioning
confidence: 99%